A Dynamic Role of Mastermind-Like 1: A Journey Through the Main (Path)ways Between Development and Cancer - Zema, Sabrina; Pelullo, Maria; Nardozza, Francesca; Felli, Maria Pia; Screpanti, Isabella; Bellavia, Diana (Frontiers in Cell and Developmental Biology, 2020)
Major signaling pathways, such as Notch, Hedgehog (Hh), Wnt/-catenin and Hippo, are targeted by a plethora of physiological and pathological stimuli, ultimately resulting in the modulation of genes that act coordinately to establish specific biological processes. Many biological programs are strictly controlled by the assembly of multiprotein complexes into the nucleus, where a regulated recruitment of specific transcription factors and coactivators on gene promoter region leads to different transcriptional outcomes. MAML1 results to be a versatile coactivator, able to set up synergistic interlinking with pivotal signaling cascades and able to coordinate the network of cross-talking pathways. Accordingly, despite its original identification as a component of the Notch signaling pathway, several recent reports suggest a more articulated role for MAML1 protein, showing that it is able to sustain/empower Wnt/-catenin, Hh and Hippo pathways, in a Notch-independent manner. For this reason, MAML1 may be associated to a molecular “switch”, with the function to control the activation of major signaling pathways, triggering in this way critical biological processes during embryonic and post-natal life. In this review, we summarize the current knowledge about the pleiotropic role played by MAML proteins, in particular MAML1, and we recapitulate how it takes part actively in physiological and pathological signaling networks. On this point, we also discuss the contribution of MAML proteins to malignant transformation. Accordingly, genetic alterations or impaired expression of MAML proteins may lead to a deregulated crosstalk among the pathways, culminating in a series of pathological disorders, including cancer development. Given their central role, a better knowledge of the molecular mechanisms that regulate the interplay of MAML proteins with several signaling pathways involved in tumorigenesis may open up novel opportunities for an attractive molecular targeted anticancer therapy.